Colorectal cancer genetic variants are also associated with serrated polyposis syndrome susceptibility. Issue 10 (13th March 2020) - Arnau-Collell, Coral; Soares de Lima, Yasmin; Díaz-Gay, Marcos; Muñoz, Jenifer; Carballal, Sabela; Bonjoch, Laia; Moreira, Leticia; Lozano, Juan José; Ocaña, Teresa; Cuatrecasas, Miriam; Díaz de Bustamante, Aranzazu; Castells, Antoni; et al.
Abstract : Background: Serrated polyposis syndrome (SPS) is a clinical entity characterised by large and/ormultiple serrated polyps throughout the colon and increased risk for colorectal cancer (CRC). The basis for SPS genetic predisposition is largely unknown. Common, low-penetrance genetic variants have been consistently associated with CRC susceptibility, however, their role in SPS genetic predisposition has not been yet explored. Objective: The aim of this study was to evaluate if common, low-penetrance genetic variants for CRC risk are also implicated in SPS genetic susceptibility. Methods: A case-control study was performed in 219 SPS patients and 548 asymptomatic controls analysing 65 CRC susceptibility variants. A risk prediction model for SPS predisposition was developed. Results: Statistically significant associations with SPS were found for seven genetic variants (rs4779584- GREM1, rs16892766- EIF3H, rs3217810- CCND2, rs992157- PNKD1 / TMBIM1, rs704017- ZMIZ1, rs11196172- TCF7L2, rs6061231- LAMA5 ). The GREM1 risk allele was remarkably over-represented in SPS cases compared with controls (OR=1.573, 1.21–2.04, p value=0.0006). A fourfold increase in SPS risk was observed when comparing subjects within the highest decile of variants (≥65) with those in the first decile (≤50). Conclusions: Genetic variants for CRC risk are also involved in SPS susceptibility, being the most relevant ones rs4779584- GREM1, rs16892766- EIF3H and rs3217810- CCND2 .